Art 1983 Analysis of the Effectiveness of Facilities and Infrastructure Management at PT Kereta Api Indonesia (Persero) Regional Division I, North Sumatra - Tasya Umaira; Nur Ahmadi Bi Rahmani; Atika (IAI Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2026)
This study aims to analyze the effectiveness of facilities and infrastructure management at PT Kereta Api Indonesia (Persero) Regional Division I of North Sumatra from the perspective of railway service users at Medan Station. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observation, and document analysis, and analyzed thematically. The findings indicate that the effectiveness of facilities and infrastructure management is perceived not merely in terms of availability, but more importantly through functional consistency, accessibility, and maintenance practices in service delivery. Although the management of facilities and infrastructure is considered reasonably effective in supporting basic railway services, limitations remain in terms of functional sustainability and alignment with users’ needs. This study highlights the importance of user perspectives as external indicators in evaluating the effectiveness of public transportation facilities and infrastructure management.